The Influence of Electronic Word of Mouth and Celebrity Endorsers on Purchase Intention with Personality as a Moderating Variable in the Shopee Marketplace - Steffiani Alodia; Kristiningsih (P3I UMSurabaya, 2024)
The presence of internet technology has brought several changes to human life, especially in business environment. Currently, many people have online business through marketplaces. This change has an impact on consumer behavior, namely the tendency to shop by online. This research was conducted to test the influence of electronic word of mouth and celebrity endorsers on purchase intention with personality as a moderating variable in the Shopee marketplace. The sample in this study consisted of 100 respondents taken using non probability sampling techniques with a purposive sampling method. The results of this research state that electronic word of mouth has a significant positive effect on purchase intention and personality moderates the effect of electronic word of mouth on purchase intention. Meanwhile, celebrity endorsers does not have a significant effect on purchase intention and personality does not moderate the influence of celebrity endorsers on purchase intention. The implications of this research are useful for marketplaces in implementing strategies to create purchase intention.